The australian cerebral palsy research study – epidemiological and genetic associations with cerebral palsy. (7th June 2011) - O'Callaghan, M E; MacLennan, A H; Gibson, C S; McMichael, G L; Haan, E A; Broadbent, J; Priest, K; Goldwater, P N; Painter, J N; Montgomery, G W; Baghurst, P; Dekker, G; et al.
Abstract : Introduction: The Australian Cerebral Palsy Research Study assessed established and novel epidemiological and genetic risk factors for cerebral palsy (CP) along with their interactions. Methods: Epidemiological data were collected by maternal questionnaire and linkage to state-based perinatal repositories and CP registers. Buccal swabs from 587 case and 1154 control mother-child pairs provided DNA for assessment of 35 single nucleotide polymorphisms (SNPs). Results: Epidemiological associations with CP included: maternal infection during pregnancy (OR 1.55, 95% CI 1.26 to 1.91), small for gestational age (<10th centile, OR 4.35, 2.92 to 6.48), gestational age <32 weeks (OR 59.20, 28.87 to 121.38), multiple birth (OR 6.62, 4.00 to 10.95), a relative with CP (OR 1.61, 1.12 to 2.32), breech position (OR 2.48, 1.76 to 3.49), male gender (OR 1.68, 1.38 to 2.06), previous miscarriage (OR 2.30, 1.38 to 3.82) and illicit drug use (OR 2.22, 1.14 to 4.30). Iatrogenic heat in labour was not associated with CP outcome. No association with CP was found for 34 of the 35 SNPs studied; there was a marginal association with fetal carriage of Prothrombin gene mutation in hemiplegics born at term with a reported infection during pregnancy (p=0.0589, OR 4.52, 1.70 to 12.03 after Bonferroni correction). Multivariable analysis of CP subtypes showed family history of CP to be a risk factor in quadriplegia (OR 3.27, 1.13 to 9.45) and those born at term (OR 2.38, 1.40 to 4.06). Conclusions: The largest risk factors for CP were preterm birth, small for gestational age and multiple birth. Family history, male gender and one SNP associations suggest a genetic contribution for some cases of CP, with a possible interaction with antenatally acquired infection.